HUBUNGAN RIWAYAT PERSALINAN DENGAN TINGKAT KEJADIAN PLASENTA PREVIA PADA IBU YANG BERSALIN DI RUMAH SAKIT BUDI KEMULIAAN PERIODE 2019-2022 - Ferry Daniel Martinus; Kasih Purwati; firlya, Tanisya (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2024)
Background: Women with placenta previa are at increased risk of antepartum hemorrhage, which can be harmful to both mother and fetus. One factor that can influence the occurrence of placenta previa is trauma to the uterus, such as that caused by a cesarean sectio procedure. Methods: The method used in this study was an observational analytic with a Case-Control design conducted at Budi Kemuliaan Hospital Batam in January. The determination of the number of control and case samples used the Kelsey formula, with a total of 84 samples, with each group consisting of 42 patients. Bivariate analysis was performed to determine the Relationship Between Delivery History and the Incidence of Placenta Previa, as well as the value or magnitude of the Odds Ratio. Results: The results of this study showed that delivery history is associated with the incidence of placenta previa. The Chi-Square statistical test results showed a p-value of 0.014 (p<0.05) with an Odds Ratio of 3.100 (OR>1). Conclusion: Based on the research results, it can be concluded that there is a relationship between delivery history and the incidence of placenta previa at Budi Kemuliaan Hospital Batam. The risk of placenta previa in caesarean section is three times higher compared to normal deliveries. Keywords: Delivery History, Placenta Previa,Pregnant Women